2021
DOI: 10.3390/ijerph18030928
|View full text |Cite
|
Sign up to set email alerts
|

Add-On Effect of Postural Instructions to Abdominopelvic Exercise on Urinary Symptoms and Quality of Life in Climacteric Women with Stress Urinary Incontinence. A Pilot Randomized Controlled Trial

Abstract: The aim of this study was to investigate the add-on effect of postural instructions to an abdominopelvic exercise program on incontinence urinary symptoms (UI symptoms) and quality of life (QoL) in climacteric women with stress urinary incontinence (SUI). A randomized controlled trial was performed with a total of 40 climacteric women with SUI aged between 46 and 75 years old. Participants were randomly assigned to two groups: a group performing an abdominopelvic exercise program (AEP) (n = 20) and a group per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…According to previous studies, conventional stretching and muscle chain stretching are very effective treatments. [16][17][18] Results of the current study were supported by another research that showed that GPR and SE had similar effects on neck and upper extremity function in patients with neck pain. When evaluating groups, GPR was superior to SE in enhancing pain and quality of life.…”
Section: Discussionsupporting
confidence: 82%
“…According to previous studies, conventional stretching and muscle chain stretching are very effective treatments. [16][17][18] Results of the current study were supported by another research that showed that GPR and SE had similar effects on neck and upper extremity function in patients with neck pain. When evaluating groups, GPR was superior to SE in enhancing pain and quality of life.…”
Section: Discussionsupporting
confidence: 82%
“…To [16,17] . After that, we have further examined the formation of proximal urethral microvessels and vaginal nerve tissue morphology in rats.…”
Section: Resultsmentioning
confidence: 98%
“…Many authors recommend PFM training to increase PFM strength and endurance during the rehabilitation of pelvic floor (PF) function [10,11]. However, research has indicated that the PF does not function as an independent entity [12], and recent literature supports the use of a global approach in motor control exercise programs [13]. In addition to the PFM, PF function is also supported by the pelvis [14] and other synergistic muscles, such as the diaphragm and transversus abdominis muscles [15][16][17].…”
Section: Introductionmentioning
confidence: 99%